Longitudinal relations between parenting stress and child internalizing and externalizing behaviors: Testing within-person changes, bidirectionality and mediating mechanisms - Dijk, Willeke Van; de Moor, Marleen H. M.; Oosterman, Mirjam; Huizink, Anja C.; Matvienko-Sikar, Karen (Frontiers in Behavioral Neuroscience, 2022)
Parenthood can be experienced as a pleasant but challenging period for parents, possibly accompanied by parenting stress. Early parenthood in particular is a vulnerable period as many parents experience biological and psychosocial changes related to new parenthood. Previous studies have shown that parenting stress is related to child behavior problems, but few studies have investigated the transactional relations across time between parenting stress and child internalizing and externalizing outcomes separately, examining within-person changes. The first aim of this study was to examine the transactional within-person associations of parenting stress and child internalizing and externalizing behavior problems across childhood from age 9 months to 9 years. As a second aim, we examined parenting as a possible underlying mechanism of the transactional associations by testing whether parental warmth and hostility mediate within-person associations of parenting stress and child behavior across time. Data were analyzed from the Growing Up in Ireland longitudinal child cohort study including 7,208 caregiver-child dyads at wave 1 (child’s age nine months), who were followed at child’s age three (wave 2), five (wave 3) and nine years (wave 5). Primary caregiver’s and child’s age and gender, household income, occupational status, educational status, partner status, and cultural background were covariates assessed at all waves. Data were analyzed using a random intercept cross-lagged panel model in R-lavaan. Bidirectional relations between parenting stress and child behavior were found for both internalizing and externalizing behavior from age 5 to 9, but not for earlier time points. Our results did not indicate mediating effects of parental warmth or parental hostility in the associations between parenting stress and child behavior problems. Therefore, we conclude that parenting stress and child internalizing as well as parenting stress and child externalizing behaviors have transactional associations from child’s age 5 to 9 years. Future research examining transactional associations of parenting stress and child behaviors should investigate possible other mediations taking a within-person approach by utilizing the RI-CLPM.